Banalización de la violencia y usos políticos del culto a los « mártires » y « caídos » de la « Cruzada » en el primer franquismo - Jesús Alonso Carballés (Amnis)
This article analyses the memory devoted to the “martyrs” and “fallen soldiers” of the Spanish Civil War in the public space, based on the George L. Mosse’s “Myth of the war experience” category. The author studies the cult of the civilians and fallen soldiers as a distinguished example of the trivialization of war violence and its political uses during the early Francoism. The article focuses on the inaugurations of the war’s monuments and mausoleums built in the Basque country, paying special attention to the francoist political leader’s speeches, fiercely patriotic preachments, in which the celebrations of sacrificed people examples was elaborated as the only way to allow the dictatorship to survive.